Nilai Moral dalam Novel Bidadari Berbisik Karya Asma Nadia - Neka Nopendra; Sri Rahayu (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Moral actions are first based on the human heart itself. If the heart is not satisfied with what it has, it will be done with actions, both right and wrong actions. The research on "Analysis of Moral Values ​​in the Novel Bidadari Whispering by Asma Nadia" uses a qualitative approach with a descriptive method. This research is a type of library research with data in the form of words, sentences, and paragraphs that contain moral values ​​related to responsibility, conscience, and obligation in the novel Bidadari Berklik by Asma Nadia. Based on the results of the analysis and discussion of literary psychology, conclusions can be drawn: first, the moral value of the aspect of responsibility experienced by Ayuning's character, he has the responsibility to take care of his mother. Pak Edi's character, he has a responsibility for the safety of other people's lives, the mother character, he feels responsible for the child he found on the side of the river; second, the moral value from the aspect of conscience experienced by Ayuning's character, Ayuning's conscience is unable to suppress guilt, his tears welled up. Mother character Mother's little heart feels sad in waiting and hope. Ayuni's character, The feeling of pleasure is extraordinary when imagining that you will get a big salary if you work in the capital city. Pak Edi's character, there was a turmoil between Pak Edi's heart and mind; and third, the moral value of the aspect of obligations experienced by the Ayuning character, trying to carry out the obligation to wear the hijab for Muslim women.